2016
DOI: 10.1371/journal.pone.0153569
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CT Perfusion Biomarkers of Tumor Hypoxia

Abstract: BackgroundTumor hypoxia is associated with treatment resistance to cancer therapies. Hypoxia can be investigated by immunohistopathologic methods but such procedure is invasive. A non-invasive method to interrogate tumor hypoxia is an attractive option as such method can provide information before, during, and after treatment for personalized therapies. Our study evaluated the correlations between computed tomography (CT) perfusion parameters and immunohistopathologic measurement of tumor hypoxia.MethodsWistar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
2
4
1
Order By: Relevance
“…We found significant positive correlations between PN and E and C I at the tumor periphery in the SE images. These results are in apparent contradiction with Qi et al [ 11 ], since they found a significant negative correlation between PN and BV and BF, quantified from DCE CT images of the C6 glioma model. We hypothesize that this discrepancy is related to the differences in the kinetic models used to quantify the imaging parameters.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We found significant positive correlations between PN and E and C I at the tumor periphery in the SE images. These results are in apparent contradiction with Qi et al [ 11 ], since they found a significant negative correlation between PN and BV and BF, quantified from DCE CT images of the C6 glioma model. We hypothesize that this discrepancy is related to the differences in the kinetic models used to quantify the imaging parameters.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies of the orthotopic C6 glioma model have used DE [ 14 , 15 ] or DCE imaging techniques [ 9 , 10 , 11 ], and general findings among them are in agreement with our observations in the subcutaneous C6 glioma model. Both animal models allowed to obtain CE X-ray images that improved lesion detection and reflected the heterogeneity in E, C I , or rBV values quantified in the different tumor regions, despite the presence of the BBB in the orthotopic model, which could be explained by the similarities in microvessel morphology and permeability between these two animal models [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…46 Stroma can represent zones of hypoxia in tumors and BF and BV are negatively correlated with the degree of tumor hypoxia. 47,48 However, tumor microenvironment and its relationship with hypoxia and T A B L E 1 Median baseline perfusion parameters in different histological types of nasal tumors in dogs. vascularization in human and veterinary medicine are complex, and findings in the literature are inconsistent, and therefore assumptions should be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…To facilitate improved evaluation of treatments and to better understand tumor progression in the C6 model, numerous groups have used clinically relevant imaging tools such as positron emission tomography ( 20 ), computed tomography ( 21 ), and magnetic resonance imaging (MRI) ( 22 ). MRI has become the standard of care for the detection, staging, and assessment of treatment response in patients with glioma ( 23 ).…”
Section: Introductionmentioning
confidence: 99%